2016
DOI: 10.22487/j25805924.2016.v4.i3.6218
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Kooperatife Student Facilitator and Explaining untuk Meningkatkan Pemahaman Konsep Fisika pada Siswa Kelas X SMA Negeri 5 Palu

Abstract: Penelitian ini bertujuan untuk mengetahui peningkatan pemahaman konsep fisika antara siswa yang mengikuti model pembelajarankooperatif tipe Student Facilitator and Explaining dengan yang mengikuti pembelajaran langsung di kelas X SMA Negeri 5 Palu. Jenis penelitian yang digunakan yaitu eksperimen kuasi dengan desain “The Equivalent Pretest-Posttest Design. Populasi penelitian ini adalah seluruh siswa kelas X SMA Negeri 5 Palu. Teknik pengambilan sampel adalah purposive sampling. Kelas X MIPA 3 sebagai kelas ek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Rahayu (2020) explain that the student facilitator and explaining model can increase student involvement in class. Students become active in explaining the subject matter, discussing and gaining knowledge, and generating self-confidence (Hajar & Sukma, 2020;Ikram et al, 2022;Masjudin & Arini, 2014;Mawarsih et al, 2016;Rahayu, 2020). Students can act as assistants to help other students in a group.…”
Section: Introductionmentioning
confidence: 99%
“…Rahayu (2020) explain that the student facilitator and explaining model can increase student involvement in class. Students become active in explaining the subject matter, discussing and gaining knowledge, and generating self-confidence (Hajar & Sukma, 2020;Ikram et al, 2022;Masjudin & Arini, 2014;Mawarsih et al, 2016;Rahayu, 2020). Students can act as assistants to help other students in a group.…”
Section: Introductionmentioning
confidence: 99%
“…The SFAE learning model is useful for training students to speak in conveying their ideas or opinions. The SFAE learning model can make students active in learning (Mawarsih, Syamsu, & Kamaluddin, 2016). The model can increase insight and development of students' thinking skills because, in the learning process, there is an interaction between the teacher and students.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Zain (2013) and Nirsam et al (2013) revealed that the SFAE learning model was strongly recommended to be used as a learning innovation because it can improve student learning outcomes. Research by Rianti & Nulhakim (2017) and Mawarsih et al (2014) shows that the SFAE learning model can improve students' conceptual understanding. The SFAE learning model is effective in increasing student activity and learning achievement (Ariani 2013).…”
Section: Introductionmentioning
confidence: 99%